HUBUNGAN ANTARA GAYA ASUHAN IBU BAPA DENGAN TINGKAH LAKU DELINKUEN REMAJA DI SEKOLAH MENENGAH KEBANGSAAN PASIR GUDANG 1, JOHOR - Musleh, Noor Suhaily; Mamat, Suzyliana (Jurnal 'Ulwan, 2023)
This study aims to identify the relationship between parenting style and delinquent behaviour among students in form 4 and 5 Sekolah Menengah Kebangsaan Pasir Gudang 1, Johor. A stratified random sampling technique was used to identify 234 respondents. Research instruments Paulson’s perception of parenting style (1994) and Delinquency scale by Junger (1997) were used to see the relationship between parenting style and delinquent behaviour of teenagers. The collected data was processed using the Statistical Package for Social Sciences (SPSS ver 23). The statistical technique used in this study are percentages, Pearson’s correlation, t-test and Anova to answer the research question. The result of the study found that perenting style with delinquent behaviour of teenagers has a low correlation relationship, there is no significant difference from the aspect of gender and there is no difference from the aspect of parents’ education level.